Numerical and experimental study of hydrodynamics in a compartmented fluidized bed oil palm shell biomass gasifier - Wee, Siaw Khur (Curtin University, 2011)
Numerical and experimental studies of hydrodynamic parameters of fluidized beds formed by either a single component system or a binary mixture in a pilot plant scale model of a Compartmented Fluidized Bed Gasifier (CFBG) have been performed. The numerical study is carried out with an Eulerian-Eulerian description of both gas and particle phases and a standard drag law for multiphase interaction. The numerically simulated results are then compared with the experimental results.The 2D and 3D flow patterns of the combustor and the gasifier are first generated from the numerical study to observe the bubble formation, possible channeling behavior and the binary mixing patterns in the bed.For a single component system, detailed 3D numerical analyses and experimental studies are done to investigate the bed expansion ratio, bubble diameter, bed pressure drop, and fluidization quality in CFBG. Two types of Geldart B inert particles namely river sand and alumina are used in the study.All trends of the aforementioned studies are well-predicted with the numerical values not greater than 15% of the recorded experimental values. Good fluidization is attainable in the combustor side, while the pressure drop behaviour seen for the gasifier with river sand shows that channelling occurs in the bed. The channelling behaviour becomes more severe with alumina bed.The solid circulation rate (SCR) is numerically simulated in this study as well. Solid circulation rate (SCR) increases with the increase in bed height while the main bed aeration does not affect the SCR which is consistent with the experimental data.For a binary mixture system with palm shell and river sand as the second fluidizing material, detailed 3D numerical analysis of the bed expansion ratio is done in parallel with the experimental study. The results of numerical predictions of overall mixing quality and local mixing index are verified by comparing with the experimental results. The actual trends of the studies are modestly captured by the numerical model with under-predicted values of less than 20%. The overall binary mixing quality is enhanced with the smaller palm shell size and larger palm shell weight percent. In addition, increasing the superficial gas velocity increases the local binary mixing index in the experiment.From the studies on bed expansion, bubble formation, steady equilibrium state and overall binary mixing quality, the 2D model provides well over-predicted values compared to the 3D flow model. Also, the local mixing index of the binary system is not captured by the 2D model. The numerical values predicted by 3D model are closer to the actual values.The key findings from the aforementioned studies are used as a guide to develop and operate the pilot plant scale CFBG with 0.5 ton/day of palm shell feed for fuel gas production.